Reverse total shoulder arthroplasty for fractures and posttraumatic sequelae is associated with inferior forward elevation strength: a retrospective cohort study. Issue 1 (January 2022) - Ochsner, Mims G.; Brolin, Tyler J.; Smith, Richard; Azar, Frederick M.; Throckmorton, Thomas W.
Abstract : Background: Studies have reported excellent results with improvement in active range of motion and pain relief after reverse total shoulder arthroplasty (RTSA), but few have specifically compared the strength and range-of-motion outcomes in RTSA done for different pathologies. The purpose of this study was to determine if strength is decreased after reverse total shoulder arthroplasty (RTSA) done for degenerative conditions compared with patients with posttraumatic or acute trauma indications. Methods: Records review identified 165 patients with 2 yr of clinical follow-up after RTSA for degenerative conditions (130), posttraumatic sequelae (19), or acute proximal humeral fractures (PHF) (16). Strength in forward elevation and internal and external rotation strength were measured at final follow-up. Secondary outcomes included active range of motion, visual analog scale (VAS) pain scores, American Shoulder and Elbow Surgeon (ASES) score, Single Assessment Numerical Evaluation (SANE) score, and complication rate. Results: Forward elevation strength was 4.8 in the degenerative group, 4.25 in posttraumatic patients, and 4.33 in the acute PHF group ( P =0.036). Internal rotation strength was 4.95, 4.63, and 4.73 in the degenerative, posttraumatic, and acute PHF groups, respectively ( P =0.053). External rotation strength was 4.8, 4.50, and 4.67 in the degenerative, posttraumatic, and acute traumatic groups, respectively. There were no significant differences in range of motion, ASES scores, VAS scores, or complication rates. Conclusions: RTSA for acute PHF and posttraumatic conditions results in significantly less forward elevation strength than RTSA done for degenerative conditions. Level of Evidence: Level III.